Observations on the city tables, (particularly the second, and the alterations necessary therien) . a comparison of the second and third city tables with mr. Woolhead's table; and a proposed medius, on the principle of a regular proportion between wheat and flour.; ([London])
In: Minutes of the evidence taken before the Committee of council.